SCHOOLTEACHERS-PARENTS INTERACTIONS AMID DISTANCE AND BLENDED LEARNING: TWO-YEAR EXPERIENCE OF OVERCOMING NEGATIVE INFLUENCES OF COVID-19 PANDEMIC - Malykhin, Oleksandr; Aristova, Nataliia; Kalinina, Liudmyla (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The paper aims to show the shifts within the paradigm of schoolteachers-parents interactions amid distance and blended learning. The authors examine two-year experience of overcoming negative influence of the Covid-19 pandemic onto the system of general secondary school education. Two web-based questionnaires (for schoolteachers and for parents) were developed using Google Forms. The main objective is to get information from schoolteachers, on the one hand, and from parents, on the other hand, as for challenges they faced amid blended learning caused by the influence of the Covid-19 pandemic on the system of general secondary school education. The research methodology targeted at summarising theoretical issues on the topic and collecting empirical data comprises both the theoretical method of analysis and synthesis and the empirical method of web-based surveys. The research sample includes 2269 respondents (619 general secondary schoolteachers and 1650 parents) from different regions of Ukraine. As a general conclusion the researchers identified and substantiated the system of psychological and didactic tasks that are to be solved for harmonising further schoolteachers-parents interactions amid distance and blended learning caused by the Covid-19 pandemic. Moreover, the researchers do believe that the existing theoretical and methodological foundations of organising and providing the educational process at the stage of general secondary education are to be radically reviewed.